Lilium pumilum stress-responsive NAC transcription factor LpNAC17 enhances salt stress tolerance in tobacco - Wang, Yiping; Cui, Ying; Liu, Bin; Wang, Ying; Sun, Shaoying; Wang, Jingwen; Tan, Mengmeng; Yan, Hao; Zhang, Yanni (Frontiers in Plant Science, 2022)
Lilium pumilum is a perennial herb with ornamental edible and medicinal value. It is an excellent wild germplasm resource with wide distribution and strong resistance. The NAC family of transcription factors is unique to higher plants. The NAC family plays a regulatory role in plant growth and development and participates in plant responses to biotic and abiotic stresses. The LpNAC17 gene of L. pumilum was cloned and transformed into tobacco to investigate the response of transgenic tobacco to salt stress. The results showed that the net photosynthetic rate and contents of chlorophyll in LpNAC17 over-expressed tobacco were higher than those in the control plants, while the stomatal conductance, transpiration rate and intercellular CO2 concentration were lower than those in the controls. The activity of superoxide dismutase, peroxidase, catalase, and the content of proline in LpNAC17 over-expressed tobacco were higher than those in the controls, while the content of malondialdehyde, superoxide anion, and hydrogen peroxide were lower than that in the control. Nitro-blue tetrazolium staining and 3,3′-diaminobenzidine tissue localization showed that the contents of O2- and H2O2 in transgenic tobacco was lower than in the controls. The expression levels of NtSOD, NtPOD, NtCAT, NtHAK1, NtPMA4, and NtSOS1 in the transgenic tobacco were higher than those in the controls. Therefore, this study provides a gene source for molecular breeding of salt-tolerant plants through genetic engineering, and lays a foundation for further research on salt-tolerant Lily.